2017
DOI: 10.5812/jhealthscope.64186
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse and Its Predictors in Freshmen Students of Lorestan Universities: Subgrouping of College Students in West of Iran

Abstract: Background: Risk-taking behaviors have negative consequences on adolescents and young adults' health. Numerous studies have revealed that the prevalence of risk-taking behaviors in college students is high. However, little information is available about risktaking behaviors in freshmen students. Objectives: The present study was conducted to determine the prevalence of risk-taking behaviors and related factors in freshmen students of Khorramabad universities. Methods: This study was performed in 3 universities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It must be mentioned that the prevalence of tobacco smoking among students and adolescents in Iran and around the world, has been reported differently in the literature, ranging from 5.9% to 56% in different studies (14)(15)(16)(17)(18)(19)(20)(21)(22). However, there is an increasing trend in smoking prevalence in Iranian adolescents and the rate of becoming a smoker is high among Iranian adolescents (23).…”
Section: Introductionmentioning
confidence: 99%
“…It must be mentioned that the prevalence of tobacco smoking among students and adolescents in Iran and around the world, has been reported differently in the literature, ranging from 5.9% to 56% in different studies (14)(15)(16)(17)(18)(19)(20)(21)(22). However, there is an increasing trend in smoking prevalence in Iranian adolescents and the rate of becoming a smoker is high among Iranian adolescents (23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our findings showed that 57% of the 39 women with current WTS had started WTS in the past 1 year. A systematic review of 13 studies also showed that the prevalence of tobacco use among 5960 patients with COVID-19 in China was 1.4% to 12.6% ( 42 ) and another review study on hospitalized patients with COVID-19 reported that the prevalence of tobacco use was 7.6% ( 43 ). Tobacco use increases the risk of affliction by severe COVID-19 by 1.4 times and the risk of hospitalization an intensive care unit, the need for mechanical ventilation, and the risk of death due to COVID-19 by 2.4 times ( 44 ).…”
Section: Discussionmentioning
confidence: 98%
“…The results of a study among students in Khorramabad, Iran, showed that the prevalence rates of smoking cigarette, drug abuse, and alcohol consumption were 3.7%, 2.4%, and 5.5%, respectively [27]. Another study conducted on Tehran University students showed that the prevalence rates of alcohol, drug abuse, and high-risk sexual behaviors were 4.6%, 2.3%, and 5.6%, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study among students in Khorramabad, Iran, showed that the prevalence rates of smoking cigarette, drug abuse, and alcohol consumption were 3.7%, 2.4%, and 5.5%, respectively [27].…”
Section: Discussionmentioning
confidence: 99%